Minimum time thrust start-up of a nuclear rocket with integro-differential constraints - Pym, J.W.; Shen, C.N. (Automatica (Oxford), 1972)
The minimum time thrust start-up of a nuclear rocket gives rise to an optimal control problem where the state representing the exhaust propellant must satisfy an integro-differential equation and an inequality constraint. It is shown that by defining an appropriate Hamiltonian function, Pontryagin's Maximum Principle can be applied. The result is proved by reformulating the problem as one in the calculus of variations of minimizing a functional subject to various constraints including the two constraints mentioned above. The necessary conditions for a minimum so derived can be translated into those for a maximum principle type formulation. The results of the analysis are applied to show that boundary control is obtained for the particular problem of the nuclear rocket. La mise en route avec poussée à temps minimal d'une fusée nucléaire donne lieu à un problème de commande optimale dans lequel l'état représentant le carburant de l'échappement doit satisfaire à une equation integro-differentielle et à une contrainte sous forme d'inégalité. Il est montré que le Principe du Maximum de Pontriagin peut être appliqué en définissant une fonction hamiltonienne appropriée. Le résultat est prouvé en reformulant le problème comme étant celui d'un calcul variationnel de la minimalisation d'une fonctionnelle assujetie à diverses contraintes, dont les deux mentionnées ci-dessus. Les conditions necessaires pour un minimum ainsi obtenu peuvent être traduites en celles d'une formulation du type du principe du maximum. Les résultats de l'analyse sont appliqués pour montrer qu'une commande aux limites est obtenue pour le problème particulier de la fusée nucléaire. Der Schubstart einer nuklearen Rakete in minimaler Zeit läßt ein Problem optimaler Regelung entstehen, wo der Zustand, der den verbrauchten Treibstoff darstellt, eine Integro-Differentialgleichung und eine Beschränkung in Form einer Ungleichung befriedigen muß. Gezeigt wird, daß bei Definition einer geeigneten Hamilton-Funktion das Maximumprinzip von Pontrjagin angewandt werden muß. Das Ergebnis wurde durch Neuformulierung des Problems geprüft und zwar als ein Variationsproblem zur Minimierung eines Funktionals, das verschiedene Beschränkungen einschließlich der zwei oben erwähnten unterworfen ist. Die notwendigen Bedingungen für das so abgeleitete Minimum können in die Formulation für das Maximumprinzip überführt werden. Die Resultate der Analysis werden angewandt um zu zeigen, daß für das partikuläre Problem der nuklearen Rakete eine beschränkte Steuerung erhalten wird. зaпycк ядepнoй paкeты c нaпopoм в минимaльнoм вpeмeни пpивoдит к пpoблeмe oптимaльнoгo yпpaвлeния в кoтopoй cocтoяниe пpeдcтaвляющee coбoй вытeкaющee гopючee дoлжнo yдoвлeтвopять интeгpoдиффepeнциaльнoмy ypaвнeнию и oгpaничeнию в фopмe нepaвeнcтвa. Пoкaзывaeтcя чтo Пpинцип Maкcимyмa Пoнтpягинa мoжeт быть пpимeнeн c пoмoщью oпpeдeлeния пoдчoдящeй гaмильтoнoвcкoй фyнкции. Peзyльтaт дoкaзывaeтcя фopмyлиpyя внoвь пpoблeмy кaк зaдaчy вapиaциoннoгo вычcлeния минимизaции фyнкциoнaлa пoдвepжeннoгo paзличным oгpaничeниям, в тoм чиcлe двyм yкaзaнным вышe. Heoбчoдимыe ycлoвия для пoлyчeннoгo тaким oбpaзoм минимyмa мoгyт быть пepeвeдeны в ycлoвия фopмyлиpoвaния типa пpинципa мaкcимyмa. Peзyльтaты aнaлизa пpилaгaютcя для пoкaзaния чтo пoлyчaeтcя пpeдeльнoe yпpaвлeниe для чacтнoй пpoблeмы ядepнoй paкeты.